Why are pregnant women in Togo reluctant to undergo caesarean section? A systematic inventory of motives - Lonzozou Kpanake; Clara Mullet-Muñoz; Massima Pissa; Vissého Adjiwanou (Journal of Psychosomatic Obstetrics and Gynecology)
This study explored the reasons underlying pregnant women’s reluctance to undergo cesarean sections in Togo, despite its importance in reducing maternal and neonatal mortality. A total of 397 pregnant women who expressed hesitancy toward cesarean sections were enrolled during routine prenatal care visits at the country’s largest hospital. They completed a questionnaire comprising 72 statements addressing potential reasons for hesitancy toward cesarean sections. Their responses were analyzed using factor analysis, and the effects of participants’ demographic characteristics on scores for each factor were assessed using ANOVA. A seven-factor structure of motives was found: Fear of Death (endorsed by 92% of the sample); Regaining Autonomy Quickly (87%); Financial Concerns (74%); Fear of Stigmatization (73%); Fear of Unsupportive Reactions from Spouses and Relatives (72%); Prevention Through Spiritual Interventions (70%); and Perceived Health Risks for the Mother and Baby (40%). Scores on these factors were related to participants’ sociodemographic characteristics. Effectively addressing the low uptake of cesarean section requires a multifaceted approach rather than one focused on a single barrier. Our findings suggest critical points that could help develop tailored interventions to address the various obstacles to this life-saving care.